Menggali Makna Filsafat Pendidikan Untuk Memperkuat Kompetensi Guru dan Praktisi Pendidikan - Eva Fitriyani; Shobrun Jamil; Amalia Muflihah Rahmasari; Amalia Saharani (Jurnal Ilmiah Literasi Indonesia, 2026)
This study examines the meaning, role, and application of educational philosophy in teaching and learning activities, as well as studying various educational thoughts to understand current challenges and developments. This study aims to determine how educational philosophy can become a basis for improving the competence of teachers and educational practitioners. The method used is a qualitative research method through a literature study approach, which is carried out by collecting data from books, journals, and other scientific sources, then conducting descriptive analysis. The results of the study indicate that understanding educational philosophy can help teachers and educational practitioners to think more critically and wisely in making decisions during learning. In addition, educational philosophy can also improve professional attitudes, strengthen ethical values, and encourage innovation in the teaching and learning process. This study also found that the application of educational philosophy can help create learning that is more valuable, directed, and appropriate to the needs of students. Thus, educational philosophy certainly has a very important role in strengthening the competence of teachers and educational practitioners to be able to face these various challenges that continue to develop